A historical approach for astronomy in the context of Iniciação Científica - Xavier, Lucas Antonio; Oliveira, Fernando José Luna de; Alvarenga , Flávio Gimenes; Xavier, Mateus Geraldo; Costa, Karoline Vitória Silva da (Cadernos de Astronomia, 2023)
This article brings a synthesis of the readings on materials investigated for the scientific initiation works carried out in the university extension project. The project - Espírito Santo Astronomy Exhibition 2022, is an initiative of the Graduate Program in Astrophysics, Cosmology and Gravitation, Cosmo-Ufes Nucleus and Federal Institute of Espírito Santo. Discussions on ancient astronomy are presented, in particular on the history of Aristarchus of Samos with his measurements of sizes and distances of the Sun, the Moon and the Earth. Point out the hypotheses that led Aristarchus to propose his original heliocentric idea. Finally, the Eratosthenes model in determining the size of the Earth. With this, the learning in the scientific initiation of those involved, the student and her tutor, was positive, especially when exploring a little the history of astronomy, which can be developed in basic education in high school.